Про перiодичнi розв’язки еволюцiйних включень першого порядку з ωλ0-псевдомонотонними вiдображеннями - Касьянов, П.О. (Видавничий дім "Академперіодика" НАН України, 2008)
We consider the first-order differential-operator inclusions with operators of the ωλ0 -pseudomonotone type. The existence of periodic solutions for such inclusions by using the Faedo–Galerkin method is justified. The a priori estimates have been obtained. An example illustrating the given result has been adduced.